Development of an Arduino-based photobioreactor to investigate algae growth rate and CO2 removal efficiency - Alarde, Hans Paolo S.; Bartolabac, Kiara Jenvy C.; Acut, Dharel P.; Cane, Jas Felicisimo A.; Magsayo, Joy R. (Institute of Advanced Engineering and Science, 2022)
Global carbon dioxide (CO2) emissions are rising, and microalgae have been a primary focus for alleviating the negative impacts of increasing CO2 levels. CO2 sequestration is influenced by pH level, temperature, light, nutrient levels, and aeration. This study adapted a 2-chamber system with a 6-Liter vertical-column photobioreactor. It was constructed to remove CO2 from the air using microalgae. Arduino sensors, namely temperature, pH, and CO2 gas, were incorporated to monitor microalgal growth. Two 7-day trials, with an initial algae mass of 15 g, were implemented to investigate the growth and CO2 removal rates. The results showed that trial 1 yielded 21.5 g with a growth rate of 0.56 gxin-2 x day-1, and trial 2, a final sample of 19.7 g with a growth rate of 0.51 gxin-2 x day-1. The CO2 removal rate for trial 1 increased from 10.17% to 22.04%. However, the CO2 removal rate for trial 2 decreased from 15.66% to 3.55%. In terms of relative percent error, the Arduino sensors' accuracy was also determined to be low, ranging from 0.85 to 1.94. With accurate readings, the findings show that the CO2 removal efficiency rate and algae growth rate are directly proportional to each other.